PERAN MAHKAMAH KONSTITUSI DALAM MENJAGA SUPREMASI KONSTITUSI DI INDONESIA: The Role of the Constitutional Court in Maintaining the Supremacy of the Constitution in Indonesia - Hendro Wardana (Res Nullius Law Journal, 2026)
The Constitutional Court of Indonesia (MK) plays a strategic role in safeguarding constitutional supremacy as the foundation of the Indonesian rule of law, primarily through its authority to conduct judicial review, resolve disputes of constitutional authority, dissolve political parties, and adjudicate electoral result disputes. This article examines how the Court performs these functions while addressing challenges related to decision consistency, institutional compliance, and political dynamics affecting perceptions of judicial independence. The study introduces novelty by arguing that the Court’s role extends beyond that of a mere guardian of the constitution to that of a stabilizer within Indonesia’s evolving constitutional architecture, especially after amendments that expanded mechanisms of power control. Using a normative‑juridical research method grounded in analyses of decisions, regulations, and constitutional doctrines, this article demonstrates that strengthening the Court requires not only internal reform but also systemic support through institutional obedience and societal constitutional culture. The findings highlight that the effectiveness of the Court in maintaining constitutional supremacy depends on the integrity of its decisions, coherence of its interpretations, and its ability to distance itself from increasingly complex electoral politics.   Mahkamah Konstitusi (MK) memiliki posisi strategis dalam menjaga supremasi konstitusi sebagai pilar utama negara hukum Indonesia, terutama melalui kewenangannya melakukan pengujian undang‑undang, penyelesaian sengketa kewenangan lembaga negara, pembubaran partai politik, serta penyelesaian perselisihan hasil pemilihan umum. Artikel ini menganalisis bagaimana MK menjalankan fungsi tersebut secara efektif sekaligus mengevaluasi tantangan yang muncul terkait konsistensi putusan, kepatuhan lembaga negara, serta dinamika politik yang memengaruhi persepsi independensi lembaga. Penelitian ini menawarkan novelty berupa argumentasi bahwa peran MK tidak hanya sebagai guardian of the constitution tetapi juga sebagai stabilizer dalam arsitektur ketatanegaraan modern, terutama setelah perubahan konstitusi yang memperluas ruang kontrol terhadap kekuasaan. Dengan menggunakan metode penelitian yuridis‑normatif berbasis analisis putusan, regulasi, dan doktrin ketatanegaraan, artikel ini menunjukkan bahwa penguatan MK tidak hanya memerlukan reformasi internal, tetapi juga dukungan sistemik melalui kepatuhan institusional dan budaya konstitusional masyarakat. Hasil analisis menegaskan bahwa efektivitas MK dalam menjaga supremasi konstitusi bergantung pada integritas putusan, konsistensi tafsir, serta kemampuan MK menjaga jarak dari kontestasi politik elektoral yang kian kompleks.